Comparison of sweetness in ear corn with different genetic background and incorporation of the shrunken2 gene - López-Hernández, Alexander; Córdova-Téllez, Leobigildo; Santacruz-Varela, Amalio; García-Zavala, J. Jesús (Revista Mexicana de Ciencias Agrícolas, 2023)
The production of super sweet ear in Mexico focuses on the use of commercial hybrids, since there are no native races with this characteristic, for this reason the following research was proposed with the objectives: a) introduce a sweetness gene in native ear corn populations; and b) determine its effect on agronomic characteristics, quality and consumer acceptance. The following native collections of ear corn were used: C-Pue-185 (Cacahuacintle), Hgo-428 (Chalqueño) and Hgo-416 (Elotes Cónicos) infiltrated with the shrunken2 gene (sh2) and with different proportions of genetic background of native corn, the commercial hybrids A7573, Cherokee and Sweeter93 were used as controls. Experiments were established in the localities of Montecillo, Texcoco, State of Mexico and San Felipe, Teotlalcingo, Puebla, in 2021, using a randomized complete block design with three repetitions. Characteristics of morphology, of yield and a sensory test were recorded. The population Hgo-428sh2F1 with genetic background 50% native + 50% super sweet was the best in terms of total soluble solids (TSS) with 16.5 ºBrix. In the sensory test, the same population Hgo-428sh2BC1F1 stood out, with genetic background of 75% native + 25% super sweet. The population formed by Hgo-428 (Chalqueño) was identified as outstanding in total soluble solids and ear flavor. The commercial hybrid A7573 stood out in morphological characteristics. The original native populations Hgo-428 (Chalqueño) and C-Pue-185 (Cacahuacintle) were equal to the best commercial control A7573 in terms of sliced fresh grain yield (SFGY). The incorporation of the super sweet gene (sh2) negatively affected all the characteristics evaluated.